2022
DOI: 10.1101/2022.01.11.475855
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rational design yields molecular insights on leaf binding of the anchor peptide Macaque Histatin

Abstract: In times of a constantly growing world population and increasing demand for food, sustainable agriculture is crucial. To reduce the amount of applied nutrients, herbicides, and fungicides, the rainfastness of plant protection agents is of pivotal importance. As a result of protective agent wash-off, plant protection is lost, and soils and groundwater are severely polluted. To date, rainfastness of plant protection products is achieved by adding polymeric adjuvants to the agrochemicals. However, polymeric adjuv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 61 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Industry-scale biodegradation was limited by the time-consuming natural processing, and as a result, enzyme discovery, protein engineering, kinetics, and computational studies provided potential solutions [129] , [130] , [131] , [132] , [133] , [134] , [135] , [136] . However, industrial application of biodegradating plastics using biocatalysts like carboxyl ester hydrolases, including lipases, esterases, cutinases, and PETases, have not been achieved yet due to a number of reasons (e.g., instability and activity reduction in even mild conditions) [133] .…”
Section: Keep Plastic Upcycling During and After Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Industry-scale biodegradation was limited by the time-consuming natural processing, and as a result, enzyme discovery, protein engineering, kinetics, and computational studies provided potential solutions [129] , [130] , [131] , [132] , [133] , [134] , [135] , [136] . However, industrial application of biodegradating plastics using biocatalysts like carboxyl ester hydrolases, including lipases, esterases, cutinases, and PETases, have not been achieved yet due to a number of reasons (e.g., instability and activity reduction in even mild conditions) [133] .…”
Section: Keep Plastic Upcycling During and After Covid-19mentioning
confidence: 99%
“…Son et al also reported a ThermoPETase variant (S121E/D186H/R280A) with remarkably enhanced thermal stability with PET degradation ability [133] . Luckily, protein engineering is not limited to altering primary sequences but offers the opportunity to design complex enzyme structures through the fusion of extra functional domains or carbohydrate-binding modules [132] . Substrate accessibility is an essential step for carboxyl ester hydrolases working on the smooth and unnotched plastic surface.…”
Section: Keep Plastic Upcycling During and After Covid-19mentioning
confidence: 99%
See 1 more Smart Citation